Fabrication of Yb-doped Lu2O3-Y2O3-La2O3 solid solutions transparent ceramics by self-propagating high-temperature synthesis and vacuum sintering. Issue 1 (January 2019) - Permin, D.A.; Balabanov, S.S.; Novikova, A.V.; Snetkov, I.L.; Palashov, O.V.; Sorokin, A.A.; Ivanov, M.G.
Abstract: A comparative analysis of sintering and grain growth processes of lutetium oxide and lutetium-yttrium-lanthanum oxides solid solutions, as well as optical properties, luminescence and laser generation of (Lux Y0.9-x La0.05 Yb0.05 )2 O3 transparent ceramics are reported. Fabrication of highly dispersed initial powders of these compounds was performed via nitrate-glycine self-propagating high-temperature synthesis (SHS) method. The powders were compacted at 300 MPa and vacuum sintered at temperatures up to 1750 °С. Optical ceramics of (Lu0.65 Y0.25 La0.05 Yb0.05 )2 O3 elemental composition were shown to have the highest in-line transmittance, which achieved 78% at the wavelength of 800 nm. Generation of laser radiation at a wavelength of 1032 nm with the differential efficiency of 20% was demonstrated in the (Lu0.65 Y0.25 La0.05 Yb0.05 )2 O3 ceramics.